Potassium and zinc improves physiological performance, nutrient use efficiency, and productivity of wheat - Nawaz, Abeer; Bashir, Muhammad Amjad; Ahmed, Wazir; Ahmad, Ijaz; Rehim, Abdur; Ikram, Rao Muhammad; Shah, Syed Shahid Hussain; Khurshid, Muhammad Yasir; Rusan, Munir Jamil; Lubani, Rashid; Saleem, Shahzad; Haq, Tanveer Ul; et al. (Frontiers in Plant Science, 2024)
Despite the critical role of balanced nutrition in crop productivity, the use of potash (K) and zinc (Zn) is not much practiced by Pakistani farmers. The reduced nutrient uptake and crop productivity together increase the costs associated with fertilization and revisit farmers' confidence in the efficacy and profitability of fertilizers. To address this problem, a field study was conducted in the research area of the MNS-University of Agriculture, Multan, in collaboration with Engro Fertilizers Limited. The research plan consisted of five treatments including T1 = Control (without N, P, K and Zn fertilizers); T2 = NP in practice (NP @ 32-23-0 kg acre-1), T3 = Recommended NP (NP @ 48-34.5 kg acre-1), T4 = Balanced NPK (NP+K @ 48-34.5-30 kg acre-1), T5 = Balanced NPK + Zn (NPK+Zn @ 48-34.5-30 + 7.5 kg acre-1). Wheat was used as a test crop and its growth, yield, physiological, and nutritional parameters were studied. Results indicated that NPK+Zn balanced nutrition increased plant height, spike length, photosynthetic rate, water use efficiency, transpiration rate, stomatal conductance, and grain yield by 13%, 15%, 44%, 60%, 63%, 39%, and 78%, respectively compared with control. It was found that the combined application of NP, K, and Zn improved the recovery efficiency of applied nutrients i.e. nitrogen recovery efficiency (NRE) by 230%, phosphorus recovery efficiency (PRE) by 136%, potassium recovery efficiency (KRE) by 135% and zinc recovery efficiency (ZnRE) by 136% as compared to NP alone application. Agronomic use efficiency of applied fertilizers such as potassium agronomic use efficiency (KAUE) by 71%, phosphorus agronomic use efficiency (PAUE) by 72%, nitrogen agronomic use efficiency (NAUE) by 70%, and zinc agronomic use efficiency (ZnAUE) by 72% as compared to NP alone application. Results showed that NPUE, PPUE, NPUE, and ZnPUE were reduced by 5%, 3%, 3%, and 5% respectively, as compared to NP alone application. Our findings suggest that K and Zn should be made an essential part of wheat nutrition management for higher yield and better quality of produce.